2008
DOI: 10.1016/j.neuroscience.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Isolation rearing impairs wound healing and is associated with increased locomotion and decreased immediate early gene expression in the medial prefrontal cortex of juvenile rats

Abstract: In addition to its maladaptive effects on psychiatric function, psychosocial deprivation impairs recovery from physical illness. Previously, we found that psychosocial deprivation, modeled by isolation rearing, depressed immediate early gene (IEG) expression in the medial prefrontal cortex (mPFC) and increased locomotion in the open field test (Levine, Youngs et al. 2007). In the present study, we examined whether similar changes in behavior and gene expression are associated with the maladaptive effects of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 80 publications
(112 reference statements)
3
28
2
Order By: Relevance
“…In the open field test, only an increased locomotor frequency was observed in both the control and experimental rats subjected to isolation, with no effect of LPS treatment. In this respect individual housing of rodents has been shown to induce hyperactivity upon exposure to a novel environment (Einon et al, 1978;Gentsch et al, 1982;Levine et al, 2008), suggesting that individually-housed rats react more vigorously (higher number of crossings) to the environmental novelty.The lack of effects on rearing frequencies and immobility time here observed probably resulted of the high variability observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the open field test, only an increased locomotor frequency was observed in both the control and experimental rats subjected to isolation, with no effect of LPS treatment. In this respect individual housing of rodents has been shown to induce hyperactivity upon exposure to a novel environment (Einon et al, 1978;Gentsch et al, 1982;Levine et al, 2008), suggesting that individually-housed rats react more vigorously (higher number of crossings) to the environmental novelty.The lack of effects on rearing frequencies and immobility time here observed probably resulted of the high variability observed.…”
Section: Discussionmentioning
confidence: 99%
“…Further in both humans and animals, over the last decade, a substantial body of literature has been developed on the neurobiological impact of early psychosocial deprivation on brain development (Comery et al, 1996;Heidbreder et al, 2000;Chugani et al, 2001;Lu et al, 2004;Teicher et al, 2004;Bianchi et al, 2006;Day-Wilson et al, 2006;Levine et al, 2007Levine et al, , 2008Schubert et al, 2009;Vitalo et al, 2009;Fabricius et al, 2010;van Harmelen et al, 2010;Han et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Having previously identified that IR rats had decreased immediate early gene (IEG) expression in the mPFC and hippocampus (Levine et al, 2007(Levine et al, , 2008Vitalo et al, 2009), we hypothesized that these regions would show decreased FDG uptake. This hypothesis was based on the fact that both PET FDG and IEG expression reflect changes in neural activity and several studies have now shown that brain imaging of neuronal activity correlates with IEG expression (Lu et al, 2004;Stark et al, 2006;Dodd et al, 2010), although IEG expression does reflect some forms of neuronal activity change that are not detected by PET imaging (Guzowski et al, 2006;Stark et al, 2006;Marrone et al, 2008;Dodd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, postweaning social and physical deprivation has measurable effects on basic behavior in rodents, though evidence is less conclusive and partly contradictory: effects range from a decrease in general activity (Roy et al, 2001) to hyperactivity in mice (Iso et al, 2007;Van de Weerd et al, 1999;Voikar, Polus, Vasar, & Rauvala, 2005;Zhu et al, 2006) and rats (Heidbreder et al, 2000;Levine et al, 2008), from decreased (Joseph & Gallagher, 1980) or unchanged (Zhu et al, 2006) exploratory behavior in rats, mice (Chapillon, Manneche, Belzung, & Caston, 1999), and female gerbils (Starkey, Normington, & Bridges, 2007), to increased play behavior in rats (Panksepp, 1981). Social deprivation can also lead to increased anxiety in male gerbils (Polaschek, 2004;Starkey et al, 2007) and mice (Voikar et al, 2005;Wolfer et al, 2004), whereas physical deprivation in C57 BL/6 mice leads to decreased anxiety (Zhu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%